Comparative performance of BEE and non-BEE mergers and acquisitions in South Africa - Mwelase, Nkanyezi (My University, 2016)
The study revisits the topic of post-acquisition performance of M&A in South Africa. Unlike preceding studies the emphasis was on target firms rather than acquiring firm and on operating performance rather than on share price reaction to M&A announcements. The study explores how operating performance is affected by BEE related M&A and non-BEE related M&A transactions. Operating performance is measured using EVA®. Economic Value Added (EVA®) reveals that target firms experienced a decline in post deal operating performance following an M&A transaction regardless of whether the M&A deal was motivated by BEE or not. The study also found that the decline in operating performance was larger for conventional (non-BEE) M&A transactions relative to BEE linked M&A transactions, though the decline was not statistically significant. Accounting based corporate performance measurement methods used to supplement the EVA® exhibit a marginal and insignificant increased in performance when the average five year post-acquisition returns are compared to the average five year pre-acquisition returns. Overall, the economic performance of target firms declined suggesting that target firms do not benefit significantly from the M&A.
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2016
Keywords: Consolidation and merger of corporations--South Africa; Employee empowerment--South Africa; Affirmative action programs--South Africa